2009
DOI: 10.1007/s00466-009-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the pervasive fracture of materials and structures using randomly close packed Voronoi tessellations

Abstract: Under extreme loading conditions most often the extent of material and structural fracture is pervasive in the sense that a multitude of cracks are nucleating, propagating in arbitrary directions, coalescing, and branching. Pervasive fracture is a highly nonlinear process involving complex material constitutive behavior, material softening, localization, surface generation, and ubiquitous contact. A pure Lagrangian computational method based on randomly close packed Voronoi tessellations is proposed as a ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 53 publications
0
33
0
1
Order By: Relevance
“… indicated that ‘ an element can be crossed by a discontinuity in such a way that one of the two resulting parts of the element becomes so small that the critical time increment for a stable solution procedure will become almost infinitesimal ’. In this general context, according to Bishop , ‘ once crack branching and crack coalescence phenomena appear , the prospect of modeling a multitude of arbitrary three‐dimensional intersecting cracks quickly becomes untenable ’.…”
Section: Introductionmentioning
confidence: 99%
“… indicated that ‘ an element can be crossed by a discontinuity in such a way that one of the two resulting parts of the element becomes so small that the critical time increment for a stable solution procedure will become almost infinitesimal ’. In this general context, according to Bishop , ‘ once crack branching and crack coalescence phenomena appear , the prospect of modeling a multitude of arbitrary three‐dimensional intersecting cracks quickly becomes untenable ’.…”
Section: Introductionmentioning
confidence: 99%
“…For two dimensional meshing problems, this angle may be randomized by moving the mesh vertex on the boundary [2], but in higher dimensions this leads to non-planar facets.…”
Section: Lemma 5 For a Non-interior Cell Touching Two Disjoint Boundmentioning
confidence: 99%
“…"Voronoi froths" because of their similar geometry to soap bubbles.) See Bishop [2] for an overview of fully Lagrangian fracture simulations over Voronoi froths, including element formulation and cell movement.…”
Section: Application Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforming polygonal finite elements [1][2][3][4] and finite elements on convex polyhedra [5][6][7] require the integration of nonpolynomial basis functions. The integration of polynomials on irregular polytopes arises in the non-conforming variable-element-topology finite element method [8,9], discontinuous Galerkin finite elements [10], finite volume element method [11] and mimetic finite difference schemes [12][13][14].…”
mentioning
confidence: 99%